21st century teaching and learning: what it entails.... / Sheela Paramasivam and Kaarthiyaini Supramaniam - Paramasivam, Sheela; Supramaniam, Kaarthiyaini (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
The onset of the Covid19 pandemic has put everyone on a learning curve, be it in the education field, business sector, or even domestic life. The restriction of movement as well as not having face to face meetings has become a real challenge for all of us. This is also the scenario in the teaching and learning domain, with both academics and students having to embrace Online Distance Education (ODL). We now have online classes, online webinars and meetings and even celebrations such as students graduation and convocation, not to mention co-curricular activities are conducted online. Various online platforms and technology is utilised to achieve this need. This then brings to mind the question: where are we heading in education, what are the challenges of the 21st century education and how is it different from the traditional setting we are so accustomed to? One of the most noticeable aspects of the 21st century classroom is that teachers are now seen as "facilitators" of student learning and not merely as "content" providers. The focus of the 21st century classroom is that students experience the environment that they will enter as 21st century workers. Thus, the need for more interdisciplinary learning as well as collaboration in all aspects of education including the industries and workforce students will enter. According to Salleh (2019), the 21st century is seen as the century of digital literacies, technological advances, multicultural societies, human mobility, global communication, social networking, innovations and creativity and inclusiveness. In other words, 21st century students need to develop the necessary 21st century skills.